2014
DOI: 10.12681/mms.938
|View full text |Cite
|
Sign up to set email alerts
|

HF Radar observations of the Dardanelles outflow current in North Eastern Aegean using validated WERA HF radar data

Abstract: A two-site WERA High Frequency radar (HF radar) system, named "Dardanos", was installed in November 2009 on the eastern coast of Lemnos Island, North Aegean Sea, to monitor the surface inflow of Black Sea waters exiting from the Dardanelles Strait, as well as to constitute a coastal management tool for incidents of oil-pollution or search-and-rescue operations. Strong interference from external radio signals has been a source of noise deteriorating the quality of the backscattered signal, thus significantly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…WERA system applied in this study has been developed at the University of Hamburg in 1996, and demonstrated robust accuracy and reliability at numerous installation sites (e.g., Helzel et al 2010Helzel et al , 2011Kokkini et al 2014). In our experiment, WERA system was used in a phased-array mode, advantageous in fjord environment where spatial and temporal variability of surface currents is relatively high.…”
Section: Data Sets and Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…WERA system applied in this study has been developed at the University of Hamburg in 1996, and demonstrated robust accuracy and reliability at numerous installation sites (e.g., Helzel et al 2010Helzel et al , 2011Kokkini et al 2014). In our experiment, WERA system was used in a phased-array mode, advantageous in fjord environment where spatial and temporal variability of surface currents is relatively high.…”
Section: Data Sets and Methodsmentioning
confidence: 95%
“…These systems are now widely accepted by the oceanographic community as an efficient tool and are routinely used by many U.S. and European oceanographic research organizations (see for example the Southern California Coastal Ocean Observing System at www.sccoos.org). The performance of HF radars has been extensively tested by comparisons with moored ADCPs, ship mounted ADCPs, drifters and models (e.g., Carbajal and Pohlmann 2004;Chapman et al 1997;Kaplan et al 2005;Kohut and Glenn 2003;Kokkini et al 2014;Ohlmann et al 2007;Shay et al 2008;Parks et al 2009;Robinson and Wyatt 2011). For example, comparisons of ADCP and WERA (Wellen Radars) estimates of surface currents at the observation network in the German Bight showed that the standard deviation between the two estimates was less than 0.1 ms -1 and the bias was -0.004 ms -1 .…”
Section: Data Sets and Methodsmentioning
confidence: 99%
“…In the Aegean Sea, offshore the eastern part of Limnos Island, an intense thermohaline front is formed between the Black Sea outflow from the Dardanelles and the Levantine Intermediate Water (LIW), which is advected from the south (Zervakis et al, 2004;Androulidakis & Kourafalou, 2011;Vervatis et al, 2011;Kokkini et al, 2014). In the eastern Alboran Sea, the Almeria -Oran convergent density front is controlled by the size and position of the Eastern Alboran Sea gyre .…”
Section: Frontsmentioning
confidence: 99%
“…Many studies comparing HF radar current measurements with in situ current measurements have been developed by researchers interested in radar performance [16][17][18][19][20][21]. Other studies that compare HF radar-derived currents with drift buoy data were also conducted over the past several years [22][23][24][25][26]. More recently, studies have been performed to develop a method of calibrating the receiving antenna (array), and promising results have also been reported for direction-finding and beam-forming HF radar systems [27].…”
Section: Introductionmentioning
confidence: 99%